1997
DOI: 10.1111/j.1365-2133.1997.tb03777.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical FK506: a potent immunotherapy for alopecia areata? Studies using the Dundee experimental bald rat model

Abstract: We elected to examine the efficacy of the topically applied immunosuppressive agent FK506 (Prograf) in the treatment of alopecia areata (AA) using the Dundee experimental bald rat (DEBR) model. Thirty lesional DEBR rats were allocated to five groups of six. Group 1 rats received 0.1 mL of a 0.25% solution of FK506 within a 2 x 2 cm marked area on one bald flank twice a week (125 micrograms FK506/cm2 per week) for 8 weeks, while the contralateral flank was left untreated. In group II, 0.05 mL of a 0.1% solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 23 publications
0
45
0
3
Order By: Relevance
“…81,82 That the potently immunosuppressive immunophilin ligand, FK506, markedly down-modulates epithelial MHC class I expression in organ-cultured human hair follicles ( Figure 1, X and Y, and Figure 2E) is a clinically most encouraging finding: on the one hand, FK506 is already widely used in clinical medicine, eg, for the suppression of liver transplant rejection, 85 on the other, FK506 has already been shown to reverse hair loss in murine and rat models of alopecia areata. 86 Therefore, the current study identifies with FK506 a widely available, registered drug that could, in principle, be tested immediately for its MHC class I down-regulating capacity in a wide range of clinical conditions where this is therapeutically desirable (eg, multiple sclerosis, 9 autoimmune uveitis, 10 mumps orchitis, 11 autoimmune chronic active hepatitis, 13,14 and alopecia areata 7,12 ). In addition, the natural, locally generated MHC class I suppressors IGF-1, TGF-␤1, and ␣-MSH, also are promising candidates for immune privilege restoration and for MHC class I suppression whenever this is clinically desired.…”
Section: Discussionmentioning
confidence: 99%
“…81,82 That the potently immunosuppressive immunophilin ligand, FK506, markedly down-modulates epithelial MHC class I expression in organ-cultured human hair follicles ( Figure 1, X and Y, and Figure 2E) is a clinically most encouraging finding: on the one hand, FK506 is already widely used in clinical medicine, eg, for the suppression of liver transplant rejection, 85 on the other, FK506 has already been shown to reverse hair loss in murine and rat models of alopecia areata. 86 Therefore, the current study identifies with FK506 a widely available, registered drug that could, in principle, be tested immediately for its MHC class I down-regulating capacity in a wide range of clinical conditions where this is therapeutically desirable (eg, multiple sclerosis, 9 autoimmune uveitis, 10 mumps orchitis, 11 autoimmune chronic active hepatitis, 13,14 and alopecia areata 7,12 ). In addition, the natural, locally generated MHC class I suppressors IGF-1, TGF-␤1, and ␣-MSH, also are promising candidates for immune privilege restoration and for MHC class I suppression whenever this is clinically desired.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was not necessary to have extensive hair loss for nail deformities to occur. Unlike human AA, extreme nail involvement resulting in near absence of McElwee/Boggess/Olivry/Oliver/Whiting/ Tobin/Bystryn/King/Sundberg [130,[153][154][155][156][157][158] DEBR rat [9,11,13,110,111] C3H/HeJ mouse [9,16,17] A C3H/HeJBir mouse substrain, developed from C3H/HeJ mice, was created for use in inflammatory bowel disease/inheritable colitis studies. This strain also develops AA in similar fashion to the C3H/HeJ strain from which it was derived with a frequency of 4.7% [95].…”
Section: Associated Conditionsmentioning
confidence: 99%
“…Studies on topical application of FK506 to mice have shown its ability to induce anagen in catagen/telogen pelage hair follicles and prolongation of the hair follicles in the anagen growth phase [108,109]. Experimentally, DEBR rats generate excellent hair regrowth with topical application of FK506, an immunomodulatory drug that may have potential as a more effective clinical treatment [110,111].…”
Section: Treatment Of Aamentioning
confidence: 99%
“…Initial trials revealed tacrolimus as a potential tool for treatment of AA [9,10]. The peculiarity of tacrolimus was the induction of anagen and hence hair growth promotion was observed with topical but not systemic route of administration.…”
Section: Tacrolimusmentioning
confidence: 99%